2017
DOI: 10.1007/s12602-017-9343-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Synbiotic Supplementation on Carotid Intima-Media Thickness, Biomarkers of Inflammation, and Oxidative Stress in People with Overweight, Diabetes, and Coronary Heart Disease: a Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Synbiotics are known to exert multiple beneficial effects, including anti-inflammatory and antioxidant actions. The aim of this study was to evaluate the effects of synbiotic supplementation on carotid intima-media thickness (CIMT), biomarkers of inflammation, and oxidative stress in people with overweight, diabetes, and coronary heart disease (CHD). This randomized, double-blind, placebo-controlled trial was conducted and involved 60 people with overweight, diabetes, and CHD, aged 50-85 years old. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Coronary atherosclerotic heart disease (CHD) is a CVD caused by stenosis or obstruction of the coronary artery [ 36 , 37 ]. It is characterized by the formation of lipid-filled atherosclerotic plaques under the tunica intima of the great and middle arteries, leading to stenosis or occlusion of the arterial lumen, which then causes myocardial ischemia and hypoxia [ 38 , 39 ].…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…Coronary atherosclerotic heart disease (CHD) is a CVD caused by stenosis or obstruction of the coronary artery [ 36 , 37 ]. It is characterized by the formation of lipid-filled atherosclerotic plaques under the tunica intima of the great and middle arteries, leading to stenosis or occlusion of the arterial lumen, which then causes myocardial ischemia and hypoxia [ 38 , 39 ].…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…Therefore, the type of bacterial strains used and even the duration of the intervention may cause differences in these results. Some other studies also showed that synbiotic supplementation could decrease hs-CRP concentration [19,33,34]. The proposed mechanism for the effect of probiotics and prebiotics on serum levels of hs-CRP is due to the extrahepatic effects of these supplements by reducing adipose tissue mass and subsequently decreasing IL-6 by adipose tissue, hepatocyte stimulation is lessened, resulting in lower amounts of hs-CRP being synthesized.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that atherosclerosis is an inflammatory disease, as abnormal activation of immune cells, excessive inflammatory mediators released, excessive inflammatory reactions, damage to coronary endothelial cells, causing platelet aggregation, thrombosis, which accelerated the formation of coronary atherosclerotic plaques, severe even porridge plaque rupture and induced myocardial infarction or acute angina attacks ( 20 ). Immune cells in patients with coronary heart disease repeatedly activated, apoptosis, resulting in decreased immune cells, impaired immune function, varying degree of decreased immune function in coronary heart disease patients.…”
Section: Discussionmentioning
confidence: 99%